2002
DOI: 10.1002/yea.860
|View full text |Cite
|
Sign up to set email alerts
|

A series of double disruptants for protein phosphatase genes in Saccharomyces cerevisiae and their phenotypic analysis

Abstract: Thirty-two protein phosphatase (PPase) genes were identified in Saccharomyces cerevisiae based on the nucleotide sequences of the entire genome. In an effort to understand the role of PPases and their functional redundancy in the cellular physiology of one of the reference eukaryotic organisms, a series of single and double PPase gene disruptants were constructed in the W303 strain background. Two single disruptants for the CDC14 and GLC7 genes were lethal. Double disruptants for 30 non-essential PPase genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 57 publications
(43 reference statements)
2
48
0
Order By: Relevance
“…Like many ribosome mutants, yvh1D cells are cold sensitive (Sakumoto et al 2002). Evidence from several previous studies supports our conclusion that Yvh1 participates in 60S ribosomal subunit biogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Like many ribosome mutants, yvh1D cells are cold sensitive (Sakumoto et al 2002). Evidence from several previous studies supports our conclusion that Yvh1 participates in 60S ribosomal subunit biogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The result is interesting in light of the fact that different functions have been implicated for this protein in previous studies. It was reported that Ppp2p is involved in the process of mitophagy (38) and confers a rapamycin-resistant function (45), and its deletion results in a caffeine-sensitive phenotype (60). We assume that these pleiotropic phenotypes are likely due to the critical role of PDC in the metabolism by supplying acetyl-CoA.…”
Section: Discussionmentioning
confidence: 80%
“…The observations that a ppz1 mutant is sensitive to calcium ions, as would be expected for a strain with higher-than-normal calcineurin activity, and that this sensitivity is fully abolished by deletion of cnb1 are in agreement with this model. It should be noted that a previous report failed to identify a ppz1 mutant as calcium sensitive (42). These authors based their work in a genetic background (W303-1A-derived strains) different from those used in this work.…”
Section: Discussionmentioning
confidence: 88%